Development of pasteurized coffee-flavored dairy beverage added with mint extract (Mentha x piperita) - Fischer, Bruno; Rauschkolb, Jean Carlo; Cansian, Rogério Luis; Fernandes, Ilizandra Aparecida; Junges, Alexander; Valduga, Eunice; Zeni, Jamile (Acta Scientiarum. Technology, 2020)
The aim of this work was to evaluate different concentrations of ethanol on antioxidant (phenolic and flavonoid) compounds extraction of Mentha x Piperita aiming at applying the extract in whey-based dairy beverages. The extracts were obtained by cold maceration using water and ethanol as solvents. The extract using water and 70% ethanol had a 13.83 (w w-1) yield, 61.72 mg GAE g-1 phenolic compounds extract, 37.27 mg QE g-1 flavonoid content extract and 0.056 mg mL-1 antioxidant activities. The dairy beverage formulations followed a 22 factorial design in order to evaluate the effect of whey/milk and starch addition on the physical-chemical (pH, acidity, moisture, ash, fat, protein, viscosity, and color) and sensorial characteristics (acceptability) of the product. Analysis of variance (ANOVA) allowed for the development and validation of mathematical models for ash content, lipids, viscosity, and luminosity of the dairy beverage. The effects of whey/milk and starch variables on such characteristics were analyzed by the elaboration of contour curves. The product presented a lower color intensity at the highest whey concentration (75%). The product had a good sensory acceptance, and the 50 whey and 50% milk formulation presented a 7.16 points average and 79.51% acceptance index, suggesting that 50% of whey could be added up to the product´s formulation.